Testimony, Responsibility and Recognition: A Ricoeurian Response to Crises of Sexual Abuse - Crowley-Buck, John (Text Matters: A Journal of Literature, Theory and Culture, 2014)
How can we, as individuals and as members of religious, educational, and/ or social institutions, more adequately respond to the crises of sexual abuse that have come to light in recent years? This paper will address this question through the philosophical lens of Paul Ricoeur. The argument proposed here is that through Ricoeur’s hermeneutics of testimony, responsibility, and recognition, we can begin to approach, address, and evaluate the crises of sexual abuse we face by grounding our ethical reflections, and actions, within a more robust philosophical framework. Therefore, this paper will proceed as follows. The first three sections will investigate Ricoeur’s writings in order to glean from them three distinct hermeneutical approaches to three different sets of criteria at play in contemporary crises of sexual abuse: first, a hermeneutics of testimony, related to memory and history; second, a hermeneutics of responsibility, related to authority and justice; and, finally, a hermeneutics of recognition, related to forgiveness and forgetting. Insofar as each of these hermeneutical approaches offers us some insight into the problematics underlying crises of sexual abuse, the fourth section will offer an evaluation of these approaches by focusing on the specific case of the sexual abuse crisis in the Catholic Church. The final section will consider possible avenues for resolution of these crises through Ricoeur’s notion of exceptional “states of peace,” at the heart of which lies mutual recognition. My hope is that this contribution provides new avenues for conversation and deliberation, as well as new resources and frameworks for articulating and implementing responsible action in the face of sexual abuse.